Imaging spin dynamics on the nanoscale using X-Ray microscopy - Stoll, Hermann; Noske, Matthias; Weigand, Markus; Richter, Kornel; Krüger, Benjamin; Reeve, Robert M.; Hänze, Max; Adolff, Christian F.; Stein, Falk-Ulrich; Meier, Guido; Kläui, Mathias; Schütz, Gisela (Frontiers in Physics, 2015)
The dynamics of emergent magnetic quasiparticles, such as vortices, domain walls, and bubbles are studied by scanning transmission x-ray microscopy (STXM), combining magnetic (XMCD) contrast with about 25 nm lateral resolution as well as 70 ps time resolution. Essential progress in the understanding of magnetic vortex dynamics is achieved by vortex core reversal observed by sub-GHz excitation of the vortex gyromode, either by ac magnetic fields or spin transfer torque. The basic switching scheme for this vortex core reversal is the generation of a vortex-antivortex pair. Much faster vortex core reversal is obtained by exciting azimuthal spin wave modes with (multi-GHz) rotating magnetic fields or orthogonal monopolar field pulses in x and y direction, down to 45 ps in duration. In that way unidirectional vortex core reversal to the vortex core 'down' or 'up' state only can be achieved with switching times well below 100 ps. Coupled modes of interacting vortices mimic crystal properties. The individual vortex oscillators determine the properties of the ensemble, where the gyrotropic mode represents the fundamental excitation. By self-organized state formation we investigate distinct vortex core polarization configurations and understand these eigenmodes in an extended Thiele model. Analogies with photonic crystals are drawn. Oersted fields and spin-polarized currents are used to excite the dynamics of domain walls and magnetic bubbles. From the measured phase and amplitude of the displacement of domain walls we deduce the size of the non-adiabatic spin-transfer torque. For sensing applications, the displacement of domain walls is studied and a direct correlation between domain wall velocity and spin structure is found. Finally the synchronous displacement of multiple domain walls using perpendicular field pulses is demonstrated as a possible paradigm shift for magnetic memory and logic applications.